Jarh Wa Ta’dil In The Review of Hadith Studies - Muhamad Chaedar Rafiq; Tajul Arifin; Tetep Abdulatip (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This paper examines in detail the Science of jarh wa al-ta'dil as a tool to assess the narrator of hadith in terms of weaknesses (jahr) and also strengths (ta'dil). The research method used is a literature study. The study resulted in that first, jarh wa ta'dil as a step to determine whether the narration of a narrator is acceptable or must be rejected altogether, the requirements and procedures in jarh wa ta'dil, and, the contradictions (khilafiyah) between al-Jarh and al-Ta'dil among scholars.